Strengthening of Cooperatives for Social Economic Transformation in Uganda - National Planning Authority (National Planning Authority, 2019)
One of Uganda’s development challenges for social economic transformation is the low production and productivity. Whereas this is manifested in all sectors of the economy, it is prominent in the agricultural sector, which is Uganda’s economic backbone. The relative productivity of labor (as measured by the value added per worker) in the agricultural sector is significantly lower than that in the non-agricultural sectors.